Asymmetric Preorganization of Inverted Pair Residues in the Sodium-Calcium Exchanger - Giladi, Moshe; Almagor, Lior; van Dijk, Liat; Hiller, Reuben; Man, Petr; Forest, Eric; Khananshvili, Daniel (Scientific reports, 2016)
In analogy with many other proteins, Na(+)/Ca(2+) exchangers (NCX) adapt an inverted twofold symmetry of repeated structural elements, while exhibiting a functional asymmetry by stabilizing an outward-facing conformation. Here, structure-based mutant analyses of the Methanococcus jannaschii Na(+)/Ca(2+) exchanger (NCX_Mj) were performed in conjunction with HDX-MS (hydrogen/deuterium exchange mass spectrometry) to identify the structure-dynamic determinants of functional asymmetry. HDX-MS identified hallmark differences in backbone dynamics at ion-coordinating residues of apo-NCX_Mj, whereas Na(+)or Ca(2+) binding to the respective sites induced relatively small, but specific, changes in backbone dynamics. Mutant analysis identified ion-coordinating residues affecting the catalytic capacity (kcat/Km), but not the stability of the outward-facing conformation. In contrast, distinct "noncatalytic" residues (adjacent to the ion-coordinating residues) control the stability of the outward-facing conformation, but not the catalytic capacity. The helix-breaking signature sequences (GTSLPE) on the α1 and α2 repeats (at the ion-binding core) differ in their folding/unfolding dynamics, while providing asymmetric contributions to transport activities. The present data strongly support the idea that asymmetric preorganization of the ligand-free ion-pocket predefines catalytic reorganization of ion-bound residues, where secondary interactions with adjacent residues couple the alternating access. These findings provide a structure-dynamic basis for ion-coupled alternating access in NCX and similar proteins.
Keywords: Archaeal Proteins; iontový transport; interakční proteinové domény a motivy; Sodium; vodík-deuteriová výměna; Hydrogen-Ion Concentration; Escherichia coli; Protein Interaction Domains and Motifs; sekvence aminokyselin; vazba proteinů; Structure-Activity Relationship; rekombinantní proteiny; Recombinant Proteins; Sodium-Calcium Exchanger; Deuterium Exchange Measurement; Amino Acid Sequence; vápník; hmotnostní spektrometrie; Ion Transport; Models, Molecular; Protein Structure, Secondary; molekulární modely; Calcium; sbalování proteinů; katalytická doména; sodík; Protein Folding; archeální proteiny; sekundární struktura proteinů; Mass Spectrometry; exprese genu; vztahy mezi strukturou a aktivitou; pumpa pro výměnu sodíku a vápníku; koncentrace vodíkových iontů; Methanocaldococcus; Protein Binding; Catalytic Domain; Gene Expression